Use of Software Development Techniques: Experiences of Brunei Darussalam - Rahim, Md. Mahbubur; A. Rahman, Mohd. Noah; H. Seyal, Afzaal (Malaysian Journal of Computer Science, 1998)
Even though a wide range of techniques are presently available to aid software development process, the actual adoption of these techniques in the industry has not been investigated widely. Existing information systems literature cites a few studies - all of which however report the experiences of US organisations. As such, little is known about how these techniques are actually being used in other parts of the world. Moreover, existing studies did not address the impact of organisational parameters on the adoption of techniques. Against this backdrop, a study was undertaken in Brunei Darussalam in 1996 to analyse the perceptions of senior Information Systems (IS) personnel regarding the use of popularly cited software development techniques within their organisations. Overall, the results indicate a low use of techniques among the Bruneian organisations. The study further confirmed the impact of size and Information Technology (IT) experience of organisations on the use of techniques, while type of organisation appeared to have no influence. The implications of these findings are discussed.